A.E. Housman : hero of the hidden life - Vincent, Edgar (The Boydell Press, 2018)
A.E. Housman (1859-1936) was both a celebrated poet and the foremost classicist of his day. His poetry was set to music by numerous composers including Arthur Somervell, Ralph Vaughan Williams, George Butterworth, Ivor Gurney, John Ireland and Samuel Barber. Housman's painstaking vocation, to restore classical manuscripts by correcting textual errors, took up virtually the whole of his working life. A seemingly inaccessible, aloof man, he never set out to be a professional poet, yet poetry poured out of him and became his monument. His renowned A Shropshire Lad and Last Poems were born of an inner crisis, sparked by a profound but unreciprocated attachment for a fellow undergraduate. To be sexually different in the time of Oscar Wilde was to invite ostracism and disgust. This fact, allied with his secretiveness and penchant for irony, reinforced his reticence on personal matters. Until now, he has remained a hidden personality, held in the public mind as prim and grim. This biography reveals by contrast a man of many facets, one companionable in small groups, generous to a fault, and always on the lookout for humour and fun; a master of English prose; a witty and compelling after-dinner speaker; an occasional writer of nonsense verse; a frequenter of the music hall; an intrepid early traveller by air; and a connoisseur of food and wine. Drawing on Housman's published letters and on 81 significant new finds, Edgar Vincent conjures up a new Housman, created out of his reactions to the events of his life as he experienced them.